Advanced Undiagnosed Abdominal Pregnancy with Good Maternal & Fetal Outcome - A Case Report (TAJ: Journal of Teachers Association, 2019)
An ectopic pregnancy is one in which the embryo implants outside the uterus. An abdominal pregnancy is a rare variety of ectopic pregnancy, Abdominal pregnancy may be primary or secondary. In primary abdominal pregnancy the initial & final implantation site is out side the uterus. But in secondary abdominal pregnancy the embryo starts out implanted in the uterus, but due to unusual circumstances such as uterine rupture the placenta grows out side the uterus. However, in most cases of abdominal pregnancy are secondary. So that, in areas where ectopic pregnancy are common the incidence of abdominal pregnancies is increased also. An abdominal pregnancy causes few symptoms. None of them are individually diagnostic, so the diagnosis depends on the sum of many clues, none of which is enough by itself. Patient may display the normal signs of pregnancy or have non-specific symptoms such as abdominal pain, vaginal bleeding and /or gastro-intestinal symptoms but frequently the diagnosis is missed. We are reporting a 35 year old lady with abdominal pregnancy with good maternal and fetal outcome.TAJ 2010; 23(1): 71-74